2015
DOI: 10.23818/limn.34.23
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition and biological colonization of native and exotic leaf litter in a Central Spain stream

Abstract: Decomposition and biological colonization of native and exotic leaf litter in a Central Spain streamRiparian invasion by exotic trees may lead to changes in the quality of leaf-litter inputs to freshwater ecosystems. Leaflitter inputs are especially important in headwater streams, where aquatic food webs largely depend on the organic matter provided by the terrestrial vegetation. In a headwater stream of Central Spain, North of Guadalajara Province (Tagus basin) we compared the decomposition and biological col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 52 publications
(86 reference statements)
0
13
1
Order By: Relevance
“…Thus, knowing the variations in physiognomy of the riparian vegetation in the Amazon Forest and the Cerrado, and that different plant species make up such riparian areas, the mycobiome is expected to reflect those differences. Other work has shown that there are different fungal communities on the leaves of different plant species in streams (Medina-Villar et al, 2015). Therefore, it should be expected that biogeographical factors may determine the intestinal microbiota of the larvae since larvae depend on plant substrates, that provide not only the nutrients but also part of the mycobiome for them.…”
Section: Influence Of the Biome On Species Distributionmentioning
confidence: 99%
“…Thus, knowing the variations in physiognomy of the riparian vegetation in the Amazon Forest and the Cerrado, and that different plant species make up such riparian areas, the mycobiome is expected to reflect those differences. Other work has shown that there are different fungal communities on the leaves of different plant species in streams (Medina-Villar et al, 2015). Therefore, it should be expected that biogeographical factors may determine the intestinal microbiota of the larvae since larvae depend on plant substrates, that provide not only the nutrients but also part of the mycobiome for them.…”
Section: Influence Of the Biome On Species Distributionmentioning
confidence: 99%
“…pseudoacacia) are among the 100 most aggressive invasive exotic species in Europe and Spain (GEIB 2006;DAISIE, 2015) and they frequently invade riparian forests in Central Spain (Castro-Díez et al 2014;Castro-Díez and Alonso 2017). As natives, Populus alba L., (Salicaceae) and Fraxinus angustifolia Vahl, (Oleaceae) were selected, because they naturally occur in the riparian habitats invaded by A. altissima and R. pseudoacacia in Central Spain (Castro-Díez et al 2014;Medina-Villar et al 2015a, 2015b, where the leaf litter sampling sites were located.…”
Section: Species Selection and Leaf Collectionmentioning
confidence: 99%
“…By contrast, leaves with a high amount of calcium may be beneficial for crustacean communities (Ohta et al 2014). Previous studies on the effects of leaf litter in aquatic ecosystems have mainly focused on the structure and function of the invertebrate and the microbial community (Cummins et al 1989;Abelho and Graça 1996;Alonso et al 2010;Bottollier-Curtet et al 2011;Medina-Villar et al 2015a;Santschi et al 2018). Less attention has been paid to the potential toxicological effects of leaf litter to particular species of aquatic organisms (Kamara and Pflugmacher 2007;Krevŝ et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, positive effects of litter could surpass the negative ones, favoring plant growth (Meisner, de Boer, Cornelissen, & van der Putten, 2012). Often, invasions by exotic trees introduce litter with different physical-chemical composition, decomposition rates and nitrogen release rates than had the native tree species replaced by them (Incerti et al, 2018;Jo, Fridley, & Frank, 2016;Medina-Villar, Alonso, Vázquez-de-Aldana, Pérez-Corona, & Castro-Díez, 2015a;Medina-Villar, Castro-Díez et al, 2015b), which could affect understory plant communities. However, it is poorly understood if differently aged litter from exotic and native tree species can have different net effects on the germination and growth of understory plants.…”
Section: Introductionmentioning
confidence: 99%
“…A. altissima and R. pseudoacacia are considered two aggressive invasive trees in Central Spain and worldwide (GEIB, 2006;Pyšek et al, 2009;Sanz-Elorza et al, 2004) and their ability to inhibit plant growth and germination by means of allelopathy has been reported (De Feo, De Martino, Quaranta, & Pizza, 2003;Nasir, Iqbal, Hiradate, & Fujii, 2005;Pisula & Meiners, 2010). Previous studies showed that litter from U. pumila, A. altissima and R. pseudoacacia had different chemical composition and/or decomposition rates than litter from co-existing native species (Alonso, González-Muñoz, & Castro-Díez, 2010;Castro-Díez, González-Muñoz, Alonso, Gallardo, & Poorter, 2009;Castro-Díez, Fierro-Brunnenmeister, González-Muñoz, & Gallardo, 2012;González-Muñoz, Castro-Díez, & Parker, 2013;Medina-Villar et al, 2015a, 2015b. Bioassays using litter leachates from A. altissima and R. pseudoacacia did not consistently show greater phytotoxicity regarding native species (Catalán et al, 2013;Medina-Villar et al, 2017).…”
Section: Introductionmentioning
confidence: 99%